PENGARUH COVID-19 TERHADAP INTERINDUSTRI DENGAN PENDEKATAN DCC-GARCH (STUDI EMPIRIS PADA PERUSAHAAN TERCATAT DI EMERGING MARKETS) - Chikita Tiara Griska; Muhammad Ridwan (Fakultas Ekonomi Universitas Tridinanti Palembang, 2022)
The uncertainty caused by the presence of the COVID-19 pandemic has caused the world economy to suffer huge losses. This study aims to prove that COVID-19 affects inter-industry relationships in Emerging Markets using the DCC – GARCH approach Engle (2002). The sample used is 15 industrial sectors obtained from the period April 2019 to March 2021. The results of this study prove that the COVID-19 announcement caused high stock volatility with stock returns that declined sharply. Of the 15 industries, dynamic correlations were found across industries. The largest correlations were found in the metal & mining and steel industries while the smallest correlations were found in printing & publishing and tobacco.Keywords: COVID-19, DCC-GARCH, Volatility, Crisis, Risk.